PENGELOLAAN APLIKASI RUANG GTK (GURU DAN TENAGA KEPENDIDIKAN) DI SMK NEGERI SE-KECAMATAN KURANJI KOTA PADANG - Titin Desriani; Hade Afriansyah; Ahmad Sabandi; Novriyanti Achyar (Jurnal Manajemen Pendidikan, 2026)
Objective: GTK Room Application Management is one of the efforts to support administration, data management, and digital-based teacher competency development. This study aims to describe the management of the GTK (Teacher and Education Personnel) Room Application in State Vocational High Schools in Kuranji District, Padang City, reviewed from the aspects of planning, organizing, implementing, supervising, benefits, and supporting facilities. Method: This study uses a quantitative approach with a descriptive method. The study population is all State Vocational High School teachers in Kuranji District, Padang City. The research sample was determined using a proportional random sampling technique. Data were collected through a Likert scale questionnaire that has met the validity and reliability tests. Data were analyzed using descriptive statistics through the calculation of the average value and Respondent Achievement Level (TCR). Results: The results showed that the management of the GTK Room Application was in the good category with an average value of 4.03 and a TCR of 80.57%. The planning indicator obtained the highest value with an average of 4.40 and a TCR of 87.93%, while the supporting facilities indicator obtained the lowest value with an average of 2.71 and a TCR of 54.19%. Novelty: This study examines the management of the GTK Space Application through the aspects of planning, organizing, implementing, supervising, benefits, and supporting facilities at the Vocational High School (SMK) level.